Bullying among adolescents at the 4th State Junior High School in Yogyakarta - Rahayua, Bety Agustina; Riyaningrum , Wahyu (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Bullying among young people is a public health problem of great concern throughout the world. Inability to control emotions is often experienced in adolescence as a result of carrying out bullying behavior, which becomes negative behavior. Bullying behavior is someone who carries out aggressive actions as a form of abuse of power or power carried out to attack other people. Purpose: To provide an overview of bullying among adolescents at the 4th State Junior High School in Yogyakarta. Methods: This research used a quantitative approach with a descriptive approach. The population used in this research was students in classes VII and VIII, with a sample size of 89 respondents. The sample was taken using stratified random sampling. The data analysis technique used is univariate analysis, such as frequency distribution and percentages. Results: The results of this study showed a picture of bullying in teenagers: almost half of the students who frequently bully are 39 (43.8%), and the majority of those who do not bully are 50 (56.2%). Conclusion: Almost half of the respondents had bullied their friends, and the majority were male. Adolescent bullying should attract sufficient policy concern and practical intervention, such as a school protection system.